A rare case of spontaneous expulsive suprachoroidal haemorrhage in a glaucomatous eye treated with topical alpha-adrenergic agonist. Issue 2 (March 2023) - Pillai, Manju R; Kasthuribai, Hariharasubramanian; Ishrath, Deeba; Gnanavelu, Subathra
Spontaneous expulsive suprachoroidal hemorrhage is a rare ocular condition, which usually occurs after sudden decompression of the eyewall. Most of the cases of expulsive hemorrhage reported had a predisposing glaucoma with the combination of corneal pathology. We are reporting a case of spontaneous expulsive suprachoroidal hemorrhage in a glaucoma patient probably due to perpetuated inflammatory reaction and frequent eye rubbing induced by allergic reaction to topical alpha adrenergic agonist in a compromised cornea.